Dynamic Analysis of Trade Misinvoicing and VAT in Developing Countries : Dynamic Panel Data Model - Yanuar Irawan; Mahjus Ekananda (Yayasan Riset dan Pengembangan Intelektual, 2023)
The study aims to analyze the effect of trade misinvoicing on VAT and the role of regulatory quality in reducing the effect of trade misinvoicing on VAT. The study uses a panel data structure with a sample of 53 developing countries from 2002 to 2019. It is estimated using static and dynamic panel approaches using the GMM model. The estimation results show that trade misinvoicing significantly reduces VAT, but regulatory quality does not reduce the effect of trade misinvoicing on VAT. The study also shows that regulatory quality affects increasing VAT, and the previous period's VAT revenue also has a positive and significant effect on VAT revenue for the current period. By region group, trade misinvoicing experienced by countries in Europe & Central Asia and Middle-East & North Africa affected the decline in VAT.